Confronting Ceftolozane-Tazobactam Susceptibility in Multidrug-Resistant Enterobacterales Isolates and Whole-Genome Sequencing Results (STEP Study) - Hernández-García, M (2021)
Ceftolozane-tazobactam (C/T) is frequently used for infections caused by multidrug-resistant (MDR)-Enterobacterales isolates. Whole-genome sequencing (WGS, Illumina-Hiseq 4000/NovaSeq 6000, OGC, UK) was used to study the population structure, the resistome and the virulome of C/T-susceptible and -resistant MDR Escherichia spp. (n=30) and Klebsiella spp. (n=78) isolates, recovered from lower respiratory, intra-abdominal and urinary tract infections of ICU patients from 11 Portuguese Hospitals (STEP study, 2017-2018). Minimum inhibitory concentrations (MICs) were determined (ISO-broth microdilution, breakpoints EUCAST-2020). In Escherichia spp., a weak concordance between the phenotypic and the WGS method (P=0.051) was observed in the carbapenemase detection (3/30) [blaVIM-2 (2/3), blaKPC-3 (1/3)]; VIM-2-Escherichia coli isolates were C/T-susceptible and only the KPC-3-Escherichia marmotae producer showed C/T-resistance. Overall, CTX-M-15-E. coli-ST131-O25:H4-H30-Rx (11/30) was the most frequent subclone, followed by CTX-M-27-E. coli-ST131-O25:H4-H30 (4/4). Moreover, a wide resistome and virulome were detected in all E. coli isolates. Among Klebsiella spp. isolates [K. pneumoniae (67/78), K. aerogenes (7/78), K. oxytoca (2/78), K. variicola (2/78)], concordance (P<0.001) was observed between the phenotypic and the genomic carbapenemase detection (21/78) [blaKPC-3 (14/21), blaOXA-48 (3/21), blaOXA-181 (3/21)]. A high correlation between C/T-resistance and carbapenemase detection was established (P<0.05). Overall, a high clonal diversity was observed, mainly in KPC-3-producing K. pneumoniae isolates. An extensive resistome was detected in Klebsiella spp. isolates, whereas virulence determinants were mostly identified in carbapenemase producers (P<0.001). WGS is a powerful tool for typing characterization and microbiological study of MDR-Enterobacterales pathogens. Furthermore, carbapenemase genes are associated with C/T-resistance in Klebsiella spp., but other mechanisms might also be involved.